Synthesis and characterisation of permethylpentalene complexes and permethylpentalene derivatives - Binding, SC (2015)
This thesis expands the scope for using the permethylpentalene ligand and its precursors in the synthesis of organometallic complexes. Chapter one begins with a brief review of linked metallocenes, with which multimetallic compounds bridged by pentalene ligands have often been compared, followed by a comprehensive review of the routes used to make pentalenes and substituted pentalenes. Organometallic compounds of pentalenes are introduced, with a focus on bimetallic systems. Chapter two explores the diversification of substituents added to the permethylpentalene (Pn*) precursor WeissH4, to include ethyl and isopropyl groups. Low-symmetry mono-, di-, tri- and tetraalkylated products are formed, eight such organic molecules have been identified by NMR spectroscopy, and two characterised crystallographically. It has been demonstrated that subsequent hydrolysis and decarboxylation of two of these products produces low-symmetry alkylpentalene precursors. The chapter concludes with discussions on the selectivity exhibited in these reactions, and the assignment of stereochemistry. Chapter three describes the synthesis of the first homoleptic double metallocene complex of iron. Fe2Pn*2 has been characterised by X ray diffraction, and cyclic voltammetry studies demonstrate four accessible oxidation states (-1, 0, +1, +2). Magnetic measurements in the solid and solution state reveal an unusual triplet configuration, and DFT calculations indicate the origin of a high magnetic moment likely resides in unquenched orbital angular momentum contributions from SOMOs which have metal d character. Fe2Pn*2 is EPR silent at 5, 40, and 300 K both in solution and the solid state, suggesting a large zero-field splitting parameter. The reaction of the di-iron complex with carbon monoxide, ethylene and H2 is reported; the bimetallic CO adduct, Fe2(μ η5,η3 Pn*)(μ η5,η1 Pn*)(CO)2, has been crystallographically characterised, and contains a highly distorted allylic bonding motif, which to the author’s knowledge is believed to be unique among iron complexes. Chapter four discusses the interaction of the bidentate Pn* ligand in anti bimetallic fused metallocenes. A new ligand exchange route has been developed to access the complexes (MCp)2Pn* (M = Co, Ni), and the isostructural complexes (MCp*)2Pn* have been made for M = Fe, Co, Ni by salt metathesis reactions. All five complexes have been characterised by single crystal X-ray crystallography, and have diamagnetic ground states in solution in common with their Pn bridged analogues. Variable temperature NMR studies reveal a spin-equilibrium between S = 0 and S = 1 in the dinickel complexes. DFT calculations reproduce the spin states found, and suggest the distortion towards η3 coordination observed on crossing from Fe, to Co, to Ni, results from population of orbitals with M-bridgehead antibonding character. The electronic structures show it is important to draw comparisons between isoelectronic linked metallocenes. Electrochemical studies on the diiron, dicobalt, and (NiCp)2Pn* complexes reveal at least three redox events for each. Chapter five documents the successful synthesis and characterisation of monometallic complexes of iron and manganese with Pn*H ligands. The isostructural complexes Fe(Pn*H)2 and Mn(Pn*H)2 can have been characterised crystallographically, and are potential precursors for accessing heterometallic, and multimetallic complexes. Mn(Pn*H)2 is a rare example of a manganese sandwich compound and magnetic studies on a single isomer in the solution and solid states suggest it adopts intermediate spin states of S = 2 in solution, and S = 3/2 in the solid state. Chapter six gives experimental details for all syntheses and studies described in the preceding chapters. Chapter seven provides characterising data for all new compounds. Fitting data for VT NMR and SQUID studies are provided in the appendix at the end of this thesis. Crystallographic data in the form of .cif files, DFT output files, and raw SQUID data, can be found in the electronic appendix.